Authentic assessment in intensive training (bootcamp) of higher education students as well as feedback on the learning experience process - Taopik Barkah (Himpunan Pengembang Kurikulum Indonesia, 2024)
Authentic assessment in competency-based education should create opportunities that allow students to integrate learning and practice, resulting in mastery of the professional skills students will need in their future workplaces. Authentic assessment provides students with opportunities to engage in authentic tasks to develop, use and expand their knowledge, higher-order thinking and digital skills competencies. The role of authentic assessment in intensive training (Bootcamp) can prepare learners to improve their ability to be ready to practice when in the world of work based on tasks undertaken after completing a program in higher education. This study aims to describe the authentic form of assessment as an evaluation process used in intensive training (Bootcamp) for students to describe feedback on the Bootcamp learning experience process as consideration for improvement in the implementation of the next program. The author uses a descriptive method to provide an overview of the phenomenon studied through a literature study of existing documents. Authentic assessment activities in Bootcamp learning activities for each session per day ended with the assignment of a project called